The Influence of Work Life Balance and Skill Mapping On The Performance of BPKAD Employees in Palopo City - Saputri, Yunita Salsa; Haedar, Haedar; Kusdarianto, Indra (PT. EQUATOR SINAR AKADEMIA, 2026)
The purposeof this study is to analyze the effect of Work Life Balance and Skill Mapping on Employee Performance at the Regional Financial and Asset Management Agency (BPKAD) of Palopo City. Using a quantitative approach,this study applied multiple linear regression analysis using SPSS 22, involving 111 employees as respondents. The results of the validity test, reliability test, and multiple linear test show that Work Life Balance and Skill Mapping are valid and reliable in relation to Employee Performanceat the Regional Financial and Asset Management Agency (BPKAD) of Palopo City. The results of thet test show that Work Life Balance and Skill Mapping have a positive andsignificant effect on employee performance. The results of the F Work Life Balance and Skill Mapping tests Based on the results of statistical analysis, it can beconcluded that Work Life Balance and Skill Mapping have apositive and significant effect on employee performance. These findings are supportedby the significant F test results, while the coefficient of determination test shows that Work Life Balance and Skill Mapping have apositive and significant contribution in explaining Employee Performance.